A Quinacrine Analogue Selective Against Gastric Cancer Cells: Insight from Biochemical and Biophysical Studies. (5th December 2016) - Gomes, Ana; Fernandes, Iva; Teixeira, Cátia; Mateus, Nuno; Sottomayor, M. J.; Gomes, Paula
Abstract: One of the earliest synthetic antimalarial drugs, quinacrine, was recently reported as interesting for the treatment of acute myeloid leukemia. Inspired by this and similar findings, we evaluated a set of quinacrine analogues against gastric (MKN‐28), colon (Caco‐2), and breast (MFC‐7) cancer cell lines and one normal human fibroblast cell line (HFF‐1). All the compounds, previously developed by us as dual‐stage antimalarial leads, displayed antiproliferative activity, and one of the set stood out as selective toward the gastric cancer cell line, MKN‐28. Interestingly, this compound was transported across an in vitro MKN‐28 model cell line in low amounts, and approximately 80 % was trapped inside those cells. Nuclear targeting of the same compound and its interactions with calf thymus DNA were assessed through combined fluorescence microscopy, spectroscopy, and calorimetry studies, which provided evidence for the compound's ability to reach the nucleus and to interact with DNA. Abstract : The core of the matter : A quinacrine analogue, formerly developed as a dual‐stage antimalarial, seems to be a valuable template for additional structural optimization toward specific agents against gastric cancer. Nuclear targeting of this compound and its interactions with calf thymus DNA were assessed, and the evidence suggests that this compound has the ability to reach the nucleus and to interact with DNA.